PEMETAAN PENELITIAN ENERGI TERBARUKAN MENGGUNAKAN METODE BIBLIOMETRIK: ANALISIS KEYWORD, AUTHOR, DAN TREN PUBLIKASI - Bintang; Putri Najiha; Putri Bintang Lubis (Program Vokasi-Universitas Negeri Gorontalo, 2026)
The exponential growth in renewable energy publications makes it difficult to understand the research landscape without a systematic approach. This study applies bibliometric analysis to 17,617 Scopus documents from 2023 to 2026 using VOSviewer and Bibliometrik to map publication trends, thematic structures, and scientific collaboration networks. Results show a ±137% surge in publications from 2023 to 2025, driven by the global energy crisis and commitments from COP27/28. Five major clusters were identified, covering power systems, policy–investment–carbon, green hydrogen, energy market optimization, and storage materials, with hydrogen and artificial intelligence emerging as research frontiers. The collaboration network is dominated by intra-national patterns within China, with limited cross-regional connectivity. This study also identifies four major research gaps: energy justice, Global South collaboration, AI–hydrogen integration, and island-based ocean energy, underscoring the need for a more integrative and contextual research approach.